2018
DOI: 10.1007/s13300-018-0424-2
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review and Network Meta-Analysis Comparing Once-Weekly Semaglutide with Other GLP-1 Receptor Agonists in Patients with Type 2 Diabetes Previously Receiving 1–2 Oral Anti-Diabetic Drugs

Abstract: IntroductionOnce-weekly semaglutide is a new glucagon-like peptide-1 (GLP-1) analogue administered at a 1.0 or 0.5 mg dose. As head-to-head trials assessing once-weekly semaglutide as an add-on to 1–2 oral anti-diabetic drugs (OADs) vs other GLP-1 receptor agonists (GLP-1 RAs) are limited, a network meta-analysis (NMA) was performed. The objective was to assess the relative efficacy and safety of once-weekly semaglutide vs GLP-1 RAs in patients with type 2 diabetes (T2D) inadequately controlled on 1–2 OADs.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 71 publications
4
44
0
1
Order By: Relevance
“…To our knowledge, this is the first systematic review and meta‐analysis to assess the totality of the available evidence base supporting use of semaglutide in everyday clinical practice. In line with our findings, an isolated industry‐funded network meta‐analysis, with a narrower scope, recently compared semaglutide to other GLP‐1 RAs and showed that semaglutide was superior in terms of HbA1c lowering and body weight reduction, with a similar risk of adverse effects . Similarly, an industry‐funded pooled analysis summarized existing evidence from a subset of SUSTAIN trials .…”
Section: Discussionsupporting
confidence: 85%
“…To our knowledge, this is the first systematic review and meta‐analysis to assess the totality of the available evidence base supporting use of semaglutide in everyday clinical practice. In line with our findings, an isolated industry‐funded network meta‐analysis, with a narrower scope, recently compared semaglutide to other GLP‐1 RAs and showed that semaglutide was superior in terms of HbA1c lowering and body weight reduction, with a similar risk of adverse effects . Similarly, an industry‐funded pooled analysis summarized existing evidence from a subset of SUSTAIN trials .…”
Section: Discussionsupporting
confidence: 85%
“…The SUSTAIN 8 trial (NCT03136484) will provide a head‐to‐head comparison of once‐weekly semaglutide with SGLT‐2 inhibitors (canagliflozin 300 mg). As well as in the SUSTAIN 7 trial (NCT02648204), once‐weekly semaglutide was compared with other GLP‐1 receptor agonists in the SUSTAIN 3 trial (exenatide extended‐release, NCT01885208) and in an NMA (liraglutide, dulaglutide, exenatide twice‐daily, exenatide extended‐release, lixisenatide and albiglutide) in which once‐weekly semaglutide was associated with greater reductions in HbA1c and body weight in all comparisons . Once‐weekly semaglutide was compared with basal insulin in the SUSTAIN 4 trial (NCT02128932) and was associated with significant improvements in HbA1c and body weight .…”
Section: Discussionmentioning
confidence: 99%
“…As well as in the SUSTAIN 7 trial (NCT02648204), once-weekly semaglutide was compared with other GLP-1 receptor agonists in the SUSTAIN 3 trial (exenatide extended-release, NCT01885208) and in an NMA (liraglutide, dulaglutide, exenatide twice-daily, exenatide extended-release, lixisenatide and albiglutide) in which once-weekly semaglutide was associated with greater reductions in HbA1c and body weight in all comparisons. 19,21 Once-weekly semaglutide was compared with basal insulin in the SUSTAIN 4 trial (NCT02128932) and was associated with significant improvements in HbA1c and body weight. 59 Additionally, sub-group analyses based on baseline HbA1c and BMI have shown that once-weekly semaglutide is consistently more efficacious than other treatment options included in the SUSTAIN trial programme in all sub-groups, rather than simply in groups with a high BMI at baseline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations